PRODUCTION OF FUEL MIXTURE BASED ON BREAKED SILICON - PHOSPHATE RAW MATERIAL AND CHPP WASTE - Kozhakhmetova, Aidana (Academic Scientific Journal of Chemistry, 2022)
The article provides information on man-made wastes that are environmentally hazardous and used as raw materials in the production of fertilizers in the form of a fertilizer mixture based on solid waste from various enterprises on the environment. The objects of the study are off-balance phosphorite fertilizers of small-scale composition and low-quality chemical composition and waste from the heat-and-power center with long-acting phosphorus of the Aksai deposit. Data on the mineralogical and chemical properties of industrial waste from coal mining, mining and industrial complex for the extraction of phosphate and siliceous raw materials in the Karatau phosphorite basin of the Republic of Kazakhstan are presented. The chemical and mineralogical compositions of ash and slag waste from thermal power plants, formed after the combustion of coal from the Karaganda and Ekibastuz basins, are given. The chemical and mineralogical composition of the waste of low-grade phosphate raw materials and coal ash from the Bogatyr and Maikube sections was studied using the INCA Energy Energy microhardening system using an electron microscope with a Jeol JSM-6490LV solution and HKL-Basic (Oxford Instruments) structural analysis in the laboratory of M. Auezov University. The aim of the study is to obtain a new nomenclature of environmentally safe long-acting tukosmesi with trace elements based on waste from thermal power plants and dolomitized phosphate-siliceous raw materials. In our opinion, the ash sludge (SWC) CHP contains components that possess unique technological properties that allow them to effectively use the quality of the fertilizer, so that the elements that grow properly do what they need.